2007
DOI: 10.3233/nre-2007-22308
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of functional Magnetic Resonance Imaging (fMRI) to sport concussion evaluation

Abstract: Mild traumatic brain injury (mTBI) in contact sport is a problem of such magnitude that improved approaches to diagnosis, investigation and management are urgent. Concussion has traditionally been described as a transient, fully reversible, cerebral dysfunction. However, this seemingly 'mild' injury sometimes results in long-lasting and disabling post-concussion symptoms (PCS) and abnormal neuropsychological profiles characteristic of frontal and/or temporal lobe dysfunction. At present, the pathological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Other imaging modalities, such as functional MRI (fMRI) demonstrate activation patterns that correlate with symptom severity and recovery in concussion. [10][11][12][13][14] While not part of routine assessment at the present time, they nevertheless provide additional insight to pathophysiologic mechanisms. Alternative imaging technologies (eg, positron emission tomography, diffusion tensor imaging, magnetic resonance spectroscopy, functional connectivity), while demonstrating some compelling findings, are still at early stages of development and cannot be recommended other than in a research setting.…”
Section: Concussion Investigationsmentioning
confidence: 99%
“…Other imaging modalities, such as functional MRI (fMRI) demonstrate activation patterns that correlate with symptom severity and recovery in concussion. [10][11][12][13][14] While not part of routine assessment at the present time, they nevertheless provide additional insight to pathophysiologic mechanisms. Alternative imaging technologies (eg, positron emission tomography, diffusion tensor imaging, magnetic resonance spectroscopy, functional connectivity), while demonstrating some compelling findings, are still at early stages of development and cannot be recommended other than in a research setting.…”
Section: Concussion Investigationsmentioning
confidence: 99%
“…Other imaging modalities such as fMRI demonstrate activation patterns that correlate with symptom severity and recovery in concussion. [10][11][12][13][14] Although not part of routine assessment at the present time, they nevertheless provide additional insight to pathophysiological mechanisms. Alternative imaging technologies (eg, positron emission tomography, diffusion tensor imaging, magnetic resonance spectroscopy, functional connectivity), while demonstrating some compelling findings, are still at early stages of development and cannot be recommended other than in a research setting.…”
Section: Concussion Investigationsmentioning
confidence: 99%
“…74 The cognitive symptoms of both types of injuries include deficits associated with concentration, memory, and high-level executive functions, such as planning and decision making. 54,57,74,75 It has been suggested that preparatory neural activity, i.e., attention, enables the efficient integration of sensory information and goal-based repre- sentations. 76 This theoretical framework allows PCS to be grouped into primary and secondary symptoms ( Table 2).…”
Section: A Unified Approach To Mtbimentioning
confidence: 99%